2009
DOI: 10.1021/om8010245
|View full text |Cite
|
Sign up to set email alerts
|

First Brønsted Acid-Induced Ring Expansion of an Oxaphosphirane Complex: A Combined Experimental and DFT Study

Abstract: a R denotes ubiquitous organic substituents; E denotes O or NR; [M] denotes a W(CO) 5 group. MWB(W) level. Crystallographic data of 6a and 7a have been deposited at the Cambridge Crystallographic Data Centre under the numbers CCDC-671013 (6a) and CCDC-701394 (7a). This data can be obtained free of charge from the Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_request/cif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…2 This recently changed with the advent of a facile and broadly applicable synthetic protocol based on Li/Cl phosphinidenoid complexes and their in situ reactions with carbonyl derivatives 3. 4 The first studies on ring‐expansion reactions of oxaphosphirane complexes by using strong Brønsted acids such as trifluoromethanesulfonic acid (TfOH) in the presence of nitriles enabled a P,O‐bond‐selective ring enlargement and thus access to 4,5‐dihydro‐1,3,4‐oxazaphosphole complexes;5 because of its ease, reliability, selectivity, and high yields, the protocol fulfills crucial criteria of click reactions 6. A surprising and ambiguous reactivity came to the fore if nitriles were not present7 and/or fluoroboronic acid8 was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This recently changed with the advent of a facile and broadly applicable synthetic protocol based on Li/Cl phosphinidenoid complexes and their in situ reactions with carbonyl derivatives 3. 4 The first studies on ring‐expansion reactions of oxaphosphirane complexes by using strong Brønsted acids such as trifluoromethanesulfonic acid (TfOH) in the presence of nitriles enabled a P,O‐bond‐selective ring enlargement and thus access to 4,5‐dihydro‐1,3,4‐oxazaphosphole complexes;5 because of its ease, reliability, selectivity, and high yields, the protocol fulfills crucial criteria of click reactions 6. A surprising and ambiguous reactivity came to the fore if nitriles were not present7 and/or fluoroboronic acid8 was used.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the acid‐induced ring expansion of 9 with nitriles,5 three important differences deserve special mention: 1) The formation of the intermediate [ 11 ][OTf] is less favored than the formation of the Ritter‐type adduct from the reaction of [ 9 ][OTf] with acetonitrile. This is in agreement with the weaker nucleophilicity of acetaldehyde compared to acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…[5] More recently, we developed new synthetic methodologies based on 2H-azaphosphirene complexes that provide facile access to four- [6] and five-membered [7,8] heterocycles under mild oxidative [7] or protic [8] conditions, thus introducing the "clickchemistry" concept to the field of phosphorus heterocyclic chemistry. We demonstrated that this new synthetic concept can be easily extended to oxaphosphirane [9] and azaphosphiridine [10] complex chemistry. In addition, di-and polymetallic transition metal complexes have attracted considerable interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The first designed application was found in the triflic acid induced PÀO ring expansion reaction with nitriles. [22] We accidentally discovered a thermal C À O bond cleavage reaction that provides access to novel O,P,C cage ligands. [23] As the titanium(III)-induced ring-opening of oxiranes has found numerous synthetic applications, [24] the feasibility of C À O and/or P À O bond cleavage of an oxaphosphirane complex by titanium(III) has also recently been investigated theoretically.…”
mentioning
confidence: 99%